Experimental Study on Characteristics of Bubble Point Pressure of Double-Layer Metal Screen - LIN Yilin, WANG Ye, CHEN Chengcheng, CAI Aifeng, YANG Guang, WU Jingyi (Shanghai Jiaotong Daxue xuebao)
The screen channel liquid acquisition device (LAD) has advantages in terms of energy conservation, stability, and efficiency, making it a promising application candidate in the orbit storage management system of cryogenic propellants. Improving the bubble point pressure of the screen to adapt to the low surface tension characteristics of cryogenic propellants is an important area of research. However, the increase in bubble breaking pressure of single-layer mesh screens is constrainted by material strength, transportation efficiency, and system weight, posing significant challenges. A method of forming multi-layer mesh screens through diffusion bonding to enhance the bubble point pressure of the screen is proposed. Taking a double-layer screen as an example, experiments of bubble point pressure measurement are conducted and compared with the examination of single-layer screen. The results show that the bubble point pressure increases by 10% to 20% on the double-layer mesh screen. Additionly, the experiments on the screens with different inter-layer angles are also conducted, revealing that the inter-layer angles have no significant effect on the bubble point pressure. These findings provide a new direction for design of porous screens in liquid acquisition devices.